High Human Papillomavirus Vaccine Acceptability and Cost-Effectiveness of the Chinese 2-Valent Vaccine Among Men Who Have Sex With Men: A Cross-Sectional Study in Shenyang, China - Ye, Ze-Hao; Liu, Zhao-Zhen; Cui, Si-Tong; Chu, Zhen-Xing; Jiang, Yong-Jun; Xu, Jun-Jie; Hu, Qing-Hai; Shang, Hong (Frontiers in Medicine, 2021)
Background: Despite the insupportable burden caused by the human papillomavirus and high vaccine acceptability, vaccination programs are not currently available for men who have sex with men. We aimed to assess HPV infection by examining the willingness for vaccination among MSM and cost-effectiveness of the Chinese 2-valent HPV vaccine. Methods: We recruited MSM in Shenyang, China between July and December 2020 to conduct anal HPV testing and an online survey regarding HPV-related knowledge and vaccine acceptability. We performed a cost-effectiveness analysis to evaluate the incremental cost-effectiveness ratios of the Chinese 2-valent HPV vaccine. Results: A total of 234 participants completed the online survey; of those, 203 were successfully tested for HPV. The median age was 30 years (IQR: 23–38 years). Most participants had at least undergraduate education (136/234, 58.1%). The acceptability rate for the free HPV vaccine was 57.7% (135/234). The prevalence of HPV types 16 and 18 was 14.9% (18/121) and 26.8% (22/82) in the willing and unwilling to vaccinate groups, respectively (P>0.05). The prevalence of high-risk HPV among participants aged <30 and ≥50 years was 48.6% and 38.9%, respectively. Using the Chinese per capita gross domestic product as a threshold, the Chinese 2-valent HPV vaccine would be a “very cost-effective” strategy, with an incremental cost-effectiveness ratio value of USD 4,411. This evidence showed that the Chinese 2-valent HPV vaccine was more cost-effective than other imported vaccines. Conclusions: Targeted strategies should be utilized in MSM with different rates of vaccine acceptability. A pilot HPV vaccination program based on the Chinese 2-valent HPV vaccine for MSM is urgently warranted to reduce the burden of HPV and anal cancer.